Advertising Effectiveness through Message Strategies- A Case Study of Airtel - Makkar, Urvashi (Indian Journal of Marketing, 2005)
Sunil Bharti Mittal, the founder-chairman of Bharti Enterprises (which owns Airtel), is today, the most celebrated face of the telecom sector in India. He symbolizes the adage that success comes to those who dream big and then work assiduously to deliver it. Sunil Bharti Mittal began his journey manufacturing spare parts for bicycles in the late 1970s. His strong entrepreneurial instincts gave him a unique flair for sensing new business opportunities. In the early years, Bharti established itself as a supplier of basic telecom equipment. His true calling came in the mid 1990s when the government opened up the sector and allowed private players to provide telecom services. Bharti Enterprises accepted every opportunity provided by this new policy to evolve into India’s largest telecommunications company and one of India’s most respected brands. Airtel was launched in 1995 in Delhi. In the ensuing years, as the Airtel network expanded to several parts of India, the brand came to symbolize the very essence of mobile services.